2019
DOI: 10.3390/ijerph17010133
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Healthy Green Spaces, Psychological Resilience, Attitude, Brand Attachment, and Price Reasonableness in Increasing Hotel Guest Retention

Abstract: The present research was an empirical endeavor to explore the effect of green spaces on the traveler retention process and to establish a theory connecting such green spaces, psychological resilience, attitude, brand attachment, and retention in the hotel industry. A quantitative approach was employed to achieve study objectives. Our findings from the structural analysis indicated that green spaces as nature-based solution significantly influence psychological resilience. In addition, such relationship contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 49 publications
(155 reference statements)
1
16
0
Order By: Relevance
“…Green design—along with the green physical environments—has been a fundamental topic in the diverse business sectors for the past few decades [ 1 , 2 , 3 ]. The green physical environments of a building—as well known as biophilic atmospherics—are considered as a significant instance of nature-based solutions for occupant mental/emotional health [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Green design—along with the green physical environments—has been a fundamental topic in the diverse business sectors for the past few decades [ 1 , 2 , 3 ]. The green physical environments of a building—as well known as biophilic atmospherics—are considered as a significant instance of nature-based solutions for occupant mental/emotional health [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Green design—along with the green physical environments—has been a fundamental topic in the diverse business sectors for the past few decades [ 1 , 2 , 3 ]. The green physical environments of a building—as well known as biophilic atmospherics—are considered as a significant instance of nature-based solutions for occupant mental/emotional health [ 3 , 4 , 5 , 6 ]. Indeed, the effective use of the green design of a company can result in decreased anxiety/stress and increased comfort/well-being among the visitors [ 7 , 8 , 9 ] particularly in the service consumption situation [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, some studies have shown that fierce product market competition not only increases the business risk of auditors but also increases the business risk of customers. Auditors are responsible for discovering material misstatements and confidently issuing audited financial statements (Yu, 2020). If auditors cannot use standard audit procedures to reduce the risk of customer breaches or errors to acceptable levels, they will require payment of insurance premiums to compensate.…”
Section: Introductionmentioning
confidence: 99%